Psycholgical Expressives in the Koranic Stories - دزه يي دلخوش جارالله حسين; عزيز سوزان رضا (Al-Adab Journal, 2019)
This papers aims at analyzing the stories provided in the Holy Koran in the light of the Speech Act Theory. Special attention is paid to psychological expressives. The paper consists of an introduction, which explains the nature, aims, and procedures of this study, an overview of expressive speech acts, and two sections devoted to dealing with direct and indirect psychological expressives, respectively. Finally, the papers end with some conclusions drawn from the analyses.